Two-Dimensional Carbon-Coated Graphene/Metal Oxide Hybrids for Enhanced Lithium Storage - Su, Yuezeng; Li, Shuang; Wu, Dongqing; Zhang, Fan; Liang, Haiwei; Gao, Pengfei; Cheng, Chong; Feng, Xinliang (ACS nano, 2012)
Metal oxides (MOs) have been widely investigated as promising high-capacity anode material for lithium ion batteries, but they usually exhibit poor cycling stability and rate performance due to the huge volume change induced by the alloying reaction with lithium. In this article, we present a double protection strategy by fabricating a two-dimensional (2D) core–shell nanostructure to improve the electrochemical performance of metal oxides in lithium storage. The 2D core–shell architecture is constructed by confining the well-defined graphene based metal oxides nanosheets (G@MO) within carbon layers. The resulting 2D carbon-coated graphene/metal oxides nanosheets (G@MO@C) inherit the advantages of graphene, which possesses high electrical conductivity, large aspect ratio, and thin feature. Furthermore, the carbon shells can tackle the deformation of MO nanoparticles while keeping the overall electrode highly conductive and active in lithium storage. As the result, the produced G@MO@C hybrids exhibit outstanding reversible capacity and excellent rate performance for lithium storage (G@SnO2@C, 800 mAh g–1 at the rate of 200 mA g–1 after 100 cycles; G@Fe3O4@C, 920 mAh g–1 at the rate of 200 mA g–1 after 100 cycles).